IMPLEMENTASI MULTIMEDIA INTERAKTIF BERBASIS ANDROID MATERI FAKTOR BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V MI TARBIYATUL ULUM - Chofifah Dwi Aprilia; Wahyu Henky Irawan; A. Nurul Kawakip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is a fundamental subject that plays a crucial role in developing logical and systematic thinking skills. However, many students struggle to understand mathematical concepts in practice, particularly in topics like number factors, including the Least Common Multiple (LCM) and Greatest Common Factor (GCF). This difficulty often arises due to reliance on conventional teaching methods, such as lectures and repetitive exercises, with limited media like textbooks and whiteboards. Such an approach reduces student motivation and hinders their comprehension of LCM and GCF. This study aims to determine whether the Android-based interactive multimedia